Use of New Pedagogical Technologies in Russian Language Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scientific article discusses the advantages of using modern pedagogical and innovative technologies in teaching Russian language classes. The article examines the opinions of a number of scientists on this issue and tries to clarify the optimal methodology for increasing the effectiveness of the lesson.